Sezonske spremembe gladine Cerkniškega jezera v obdobju 1961–2020 - Miklič, Stanka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
In this article, we analyse the annual changes in the minimum (Hnp), mean (Hs) and maximum (Hvp) water levels of Cerknica Lake in the period 1961–2020 and try to relate them to changes in the local climate. Lower precipitation, higher temperatures and the resulting higher evaporation as well as a reduced influence of snow retention are reflected in the changing discharge from the lake basin, which is a cause of a decrease in annual, spring and summer Hs and Hvp, while winter and fall Hs and Hvp have remained at a similar level. On the other hand, Hnp increases, except in spring, which is on an annual basis, in summer and fall (as far as the unreliability of data at the lowest water levels allows) probably due to artificial retention of water in the lake, and in winter and spring due to climate change.
Keywords: Cerkniško jezero; climate change; hidrogeografija; hydrogeography; jezera; lake water regime; lakes; podnebne spremembe; Slovenia; Slovenija